Locating Police Service Points in the Rural Areas of Limpopo, South Africa - Webber, Kirsten (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2015)
Thesis (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2012.